Fenomén etnickej menšiny: Na príklade Bratislavy v 1. polovici 20. storočia - Salner, Peter; Luther, Daniel (Lidé města, 2000)
Using the example of Jewish community in Bratislava the paper deals with the problem of ethnic minority in the course of the 20th century. The selection of the locality is consistent with zhe multicultural nature of the environment under observation and its gradual transformation in the course of time. Statistical data have confirmed that there were numerous communities of ethnic Slovaks, Hungarians, Germans and Jews in the city. Their quantitative relationship, mutual relations as well as the position within Bratislava's hierarchy were changing depending on the political situation of the given state (Austro-Hungarian Empire, Czechoslovakia, wartime Slovakia, and the renewed Czechoslovakia) . The focus on the Jewish minority is a consequence of its specific and constantly changing position in society and the local community. The first part of the paper is devoted to methodological and theoretical aspects of the problem under observation. The authors submit various definitions of ethnic minority and changes in its legal position. They centered on the following phenomena: individual ethnic identity and its forming part of a group; differentiating function ot ethnicity; status of ethnic minorities; the minority status. The second part of the paper (subchapter Undifferentiated or differentiated minority) presents the knowledge acquired from an analysis of specific material about the Jewish community in Bratislava. The researchers examine the change in their position in the structure of the city, laying increased emphasis on the period after lhe Holocaust. The previous research of the problem under observation has proved that ethnicity is a factor of interna! aggression, through which various groups struggle for dominance in a community. The struggle has a polarizing character which was somewhat suppressed in tne Bratislava environment by tbe impact of several ethnic groups with their relevant importance. Their mutual interaction (expedient alliances or confrontations) mostly eliminated potential dominance of one of them. The situation changed after the dominant position in the city was gained by the Slovak communlty due to the political developments.